How to Save a Failing Project - Young, Ralph; Brady, Steve; Nagle, Dennis (Berrett-Koehler Publishers, 2009)
You CAN Turn Around A Failing Project! Poor project results are all too common and result in dissatisfied customers, users, and project staff. With countless people, goals, objectives, expectations, budgets, schedules, deliverables, and deadlines to consider, it can be difficult to keep projects in focus and on track. How to Save a Failing Project: Chaos to Control arms project managers with the tools and techniques needed to address these project challenges. The authors provide guidance to develop a project plan, establish a schedule for execution, identify project tracking mechanisms, and implement turnaround methods to avoid failure and regain control. With this valuable resource you will be able to: " Identify key factors leading to failure " Learn how to recover a failing project and minimize future risk " Better analyze your project by defining proper business objectives and goals " Gain insight on industry best practices for planning